Transforming Compassion: Examining the Development of Compassion in Nursing Who Become Patients - Carrie L. Pucino (Adult Education Research Conference, 2014)
The purpose of the study was to examine how nurses develop greater compassion in their professional practice, and examine the role of empathy in this process. Nurses report that empathy is an essential component of developing compassion. Experiences, compassionate role modeling, and self-reflection also contribute to the development of compassion.